Immunosuppressive drugs modes of action. (October 2021) - Meneghini, Maria; Bestard, Oriol; Grinyo, Josep Maria
Abstract: The innate and adaptive immune systems work as a complex interplay between different cell types, involving cytokines and chemokines mediating extracellular and paracrine effects. At the intracellular level, the inflammatory cascade is mediated by multifaceted processes that have been better described in the last 10 years. Immunosuppressive agents available in clinical practice act at different points of those cascades at the intracellular or extracellular level. Those drugs can mediate their effects on one or more cell types finally limiting inflammation and immune responses to antigens. Every immunosuppressive agent is characterized by intrinsic toxicity and side effects that may be due to the same therapeutic pathways or to off-target secondary effect of each molecule. We will here review the mechanisms of action of the most widely used immunosuppressive agents in the field of solid organ transplantation and autoimmune disorders, describing the mechanisms underlying both the therapeutic and secondary effects.